Data for "Controlling Plasmonic Catalysis via Strong Coupling with Electromagnetic Resonators" - Fojt, Jakub; Erhart, Paul; Schäfer, Christian (Chalmers University of Technology, 2024)
This upload includes the data presented and analyzed in the article "Controlling Plasmonic Catalysis via Strong Coupling with Electromagnetic Resonators" by Jakub Fojt, Paul Erhart, and Christian Schäfer.

The codes for reproducing the data are provided at doi:10.5281/zenodo.13374591.

See README.md in data.zip for a detailed description.
Keywords: Physical Sciences; Fysik